Orbital pseudolymphoma: a benign condition mimicking malignancy - Kasturi, Nirupama; Kaidakath, Salwa; Stephen, Mary; P., Jayasri (International Journal of Advances in Medicine, 2024)
Orbital lymphomas are not a rare condition that causes systemic and ocular morbidity, in which vision loss often occurs due to compressive optic neuropathy, and whose treatment is complex, involving chemotherapy and radiotherapy. We report a 54-year-old male with protrusion of the right eye associated with mild diminution of vision for one year, limitation of extraocular movements, and a relative afferent pupillary defect with optic disc edema. Imaging revealed a well-defined soft tissue lesion filling the retro-orbital intraconal space, suggestive of orbital lymphoma. Incisional biopsy and fine needle aspiration cytology revealed the lesion to be a reactive lymphoid hyperplasia. Following the administration of oral steroids, the patient showed significant improvement. To our knowledge, a benign lesion with an aggressive presentation is rare, and histopathology plays an important role in diagnosis and management.